Old and New Antihistamines - Wongsathuaythong, Saridiwongsa (Journal of Basic and Applied Pharmacology, 2015)
Histamines is a bioactive compound that have been identified in several organs and ti ssues in practically ani.mal series, including man. The physiological role of histamine is not clearly defined. In contrast, a very large number of experimental and clinical data indicate that histamine partly responsible for the clinical aspect of several diseases. In 1910, Dale and Laidlaw showed that the phamacological effects of histamine were comparable to the symptoms described with manifestations of immediate hypersensitivity Histamine is stored in the mast cells.These cells are present in the perivascular space of several organs, and are present in great quantity in the nasal and ocular mucous membranes, in the bronchial and pulmonary tissue,and in the skin. It is acknowledged the the degranulation of mast cells associated with release of histamine is a fundamental mechanism responsible for the clinical allergic conditions. According to the localization of the phenomenon, various allergic manifestations are observed; they are mainly present at two level: the respira tory level (rhinitis and asthma) and the cutaneous level (urticaria). lnhbition of the activity of histamine in these various diseas will produce a definite therapeutic effect.The first antihistaminic substances were synthesized between 1937 and 1944. The clinical use of antihistamines was generalized after World War II. Their use and clinical efficacy are limited by pharmacological properties other than their antihistaminic activity. These additional effects include : an anticholinergic activi ty, a local anaethetic activity, and a depressant activity at the level of the central nervous sytem (CNS). Conventional antihistamines do not inhibit some of the pharmacological effects of histamine. Ash and Schild were the first to put forward the concept of two different receptors for histamine. Black et al confirmed the existence of a second recptor (H2) for histamine, responsible for the effect of histamine on gastric secretion. Since then specific anti-H2 substances have been developed and are used mainly for the treatment of peptic diseases. A recently described H3 receptor is thought, to be implicated in histamine's regulation of its own synthesis and release from central and peripheral nerve tissue. In recent years, H1 antihistamine have been developed that have little or no CNS depressant effect. This class of drugs are the non-sedating H1 antagonists. Their lack of the sedating properties that are so characteristic of earlier H1 blockers has been ascribed to their very limited ability to cross the blood-brain barrier.